PENGARUH NON PERFORMING FINANCING, DANA PIHAK KETIGA, DAN INFLASI TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH - Sari, Maulita; Made, Anwar; Setiyowati, Supami Wahyu (Jurnal Riset Mahasiswa Akuntansi, 2017)
The purpose of this study is to examine and explain the effect of Non Performing Financing, ThirdParty Funds and Inflation on the profit sharing rate of mudharabah deposits at banks registered with BankIndonesia (BI) in 2015-2016. The population of this research is the Sharia Commercial Bank (BUS) registeredat Bank Indonesia. Sampling using a purposive sampling method. In order to obtain a sample of four banks.Researchers use secondary data in the form of time series data (time series). Methods of observation for twoyears (2015-2016). Analysis of the data used in this study is the classic assumption test and hypothesis test. Theresearch method used in this research is the explanatory research method. While the analytical method used ismultiple linear regression analysis. The results of this study indicate that the Non Performing Financing andInflation variables for the mudharabah deposit profit sharing rate have a partial effect, while the Third PartyFund Variables have no effect on the profit sharing rate for mudharabah deposits. Simultaneously NPF, DPKand Inflation affect the profit sharing rate of mudharabah deposits.